DEVELOPING READING COMPREHENSION WORKBOOK FOR GRADE X HIGH SCHOOL - Annisa Damayanti; Rahmad Husein; Isli Iriani Indiah Pane (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2022)
The objective of this study was to supplement the reading comprehensionquestions by analysing the weakness regarding the levels and types of questions inthe textbook Contextual English for Grade X of Senior High Schools and todevelop a reading comprehension workbook for grade X based on Curriculum2013 and Barrett’s Taxonomy. It was found that this textbook contained too muchliteral question which was at 61.6% and only low number of high level questions(10.86%). From the preliminary finding, this workbook was then developed with210 questions and validated by teacher, lecturer, and also the students’ try out.The result of validation showed that the product was excellent. The average scorefor each aspect by the first validator was 87.36% (good) and then revise until thescore given by the second validator was 91.57% (excellent). The result ofstudents’ try out showed that the value of 0.4 on each exercises on the bookand was considered valid. From these result, it was concluded that by the designand content, the product is appropriate to be used for public.